Implementation of the First Come First Served Algorithm in the Futsal Field Booking Application using Extreme Programming - Abdillah, Muhammad Imam; Irawan, Muhammad Dedi (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
This research is related to the development of an Android-based futsal field booking application at Laut Dendang Futsal using the First Come First Serve (FCFS) method. Currently, tenants are facing problems with booking futsal fields, especially because the booking process is still manual and time consuming at Laut Dendang Futsal. Ordering systems that do not use information technology cause customers to have to visit the location directly to order the field. The FCFS method is applied to arrange a futsal field booking schedule based on order of arrival, where requests that arrive first will be served first. This research builds an Android-based application with the aim of increasing efficiency in booking management and futsal field scheduling. The development approach used is the Extreme Programming method, which includes planning, design, coding and continuous testing. The results of application development show good performance in minimizing ordering errors and making it easy for Laut Dendang Futsal customers to order fields without having to come directly to the location. Admin can easily manage and record orders, avoiding errors in the ordering system. Thus, this research makes a positive contribution in increasing the efficiency of booking futsal fields, as well as speeding up responses to incidents.